Parents' Perceptions of Students' Guardians on Education Services at Yaumi Fatimah Kudus Integrated Islamic Elementary School - Adin Suryadin; Rz. Ricky Satria Wiranata; Husna Lutfiah (Journal of Contemporary Islamic Education, 2022)
The purpose of this study was to determine the extent to which parents and guardians perceive educational services at SDIT Yaumi Fatimah Kudus which include teaching services, ustadz-ustadzah services, administrative and financial services, infrastructure services, and library services. By knowing the parents' perception of the school, the school will further improve its services according to the expectations of the parents' needs. The results of research on the perceptions of parents and guardians of students towards educational services at SDIT Yaumi Fatimah in terms of learning emphasize more on moral education, the learning is interesting and in accordance with the child's development, while the ustadz-ustadz are quite professional, friendly, with educational backgrounds of almost all graduates. Administrative services are quite good, clear and transparent, only in filing a little is still lacking. The facilities and infrastructure are very adequate as a superior school, only in terms of costs, some parents still feel it is expensive. Thus, the cause of SDIT Yaumi Fatimah Kudus is a bit late in the development of the number of students because the school financing is still expensive.